Efficient and modular CRISPR‐Cas9 vector system for Physcomitrella patens - Mallett, Darren R. (John Wiley and Sons Inc., 2019)

(untitled) (Plant Direct)
CRISPR‐Cas9 has been shown to be a valuable tool in recent years, allowing researchers to precisely edit the genome using an RNA‐guided nuclease to initiate double‐strand breaks. Until recently, classical RAD51‐mediated homologous recombination has been a powerful tool for gene targeting in the moss Physcomitrella patens. However, CRISPR‐Cas9‐mediated genome editing in P. patens was shown to be more efficient than traditional homologous recombination (Plant Biotechnology Journal, 15, 2017, 122). CRISPR‐Cas9 provides the opportunity to efficiently edit the genome at multiple loci as well as integrate sequences at precise locations in the genome using a simple transient transformation. To fully take advantage of CRISPR‐Cas9 genome editing in P. patens, here we describe the generation and use of a flexible and modular CRISPR‐Cas9 vector system. Without the need for gene synthesis, this vector system enables editing of up to 12 loci simultaneously. Using this system, we generated multiple lines that had null alleles at four distant loci. We also found that targeting multiple sites within a single locus can produce larger deletions, but the success of this depends on individual protospacers. To take advantage of homology‐directed repair, we developed modular vectors to rapidly generate DNA donor plasmids to efficiently introduce DNA sequences encoding for fluorescent proteins at the 5′ and 3′ ends of gene coding regions. With regard to homology‐directed repair experiments, we found that if the protospacer sequence remains on the DNA donor plasmid, then Cas9 cleaves the plasmid target as well as the genomic target. This can reduce the efficiency of introducing sequences into the genome. Furthermore, to ensure the generation of a null allele near the Cas9 cleavage site, we generated a homology plasmid harboring a “stop codon cassette” with downstream near‐effortless genotyping.